Effect of different cowpea - cereal row to row planting systems and insecticide sprays of cowpea on the quality of the crop residues - Ajeigbe, Hakeem A.; Oseni, T.O.; Singh, B.B.; Tarawali, Shirley A. (African Crop Science Society, 2007)
A cropping system trial involving 2 spray treatments, 2 cowpea varieties, and 9 cowpea–cereals cropping patterns involving two cereals was conducted in 1999 and 2000 cropping seasons in Minjibir. The systems involved different row to row combinations of cowpea and millet or sorghum. Selected nutritive qualities of resulting cowpea and cereal stover were measured. Spraying of cowpea had no significant effect on the nutritive value of the cowpea fodder and accompanying cereal stalk. Higher proportions of cowpea in the cowpea-cereal systems improve the overall nutritive value of the resulting stover. Higher cereal proportions in the systems led to lowering of the cowpea fodder and overall digestibility. Millet stalk had higher digestibility and % P content than sorghum stalk. The crude protein yields of similar cereal systems were similar. Planting pattern had no significant effect on the crude protein content of cereals but it had significant effect on the overall crude protein yield. Increasing cowpea component in the intercropping systems increased the crude protein yield of the resulting stover.